Development and sizing of a grid-connected solar PV power plant for Canaanland community - Adeyemi A. Alabi; Anthony U. Adoghe; Oluwasikemi G. Ogunleye; Claudius O. A Awosope (Institute of Advanced Engineering and Science, 2019)
High costs of installation and maintenance as a result of storage units discourage the use of solar Photovoltaic system for power generation. To reduce these costs, Solar PV systems can be installed without storage units alongside conventional power generation systems. Such that the Solar systems cater for the daytime loads while the conventional generation system caters for loads at other times. This research paper explored the potential of installing Stand-Alone solar PV systems without storage to satisfy the daytime load demand of the Canaanland community. The load profile analysis of the Canaanland community was carried out from load consumption data and the solar power plants were designed based on this analysis. Simulation was carried out using the PV Syst 6.43 software and the result from the design was analyzed. The study revealed that the solar power plant will serve the daytime load of the community during the period of 10:30am-4:30pm daily satisfying the peak and base loads (5.16MW and 0.78MW) of the Canaanland community respectively.